N-(3-Methylphenyl)-2-nitrobenzenesulfonamide - U. Chaithanya; Sabine Foro; B. Thimme Gowda (Acta Crystallographica Section E, 2012)
In the title compound, C13H12N2O4S, the dihedral angle between the benzene rings is 73.64 (7)°. The amide H atom exhibits bifurcated hydrogen bonding: an intramolecular N—H...O hydrogen bond generates an S(7) motif while in the crystal, N—H...O(S) hydrogen bonds link the molecules into zigzag C(4) chains running along the b axis.